Evaluation of morphometric variations in mental foramen and prevalence of anterior loop in South Indian population – A CBCT study - Vani Chappidi; L A Swapna; Voulligonda Dheeraj; G R Nikitha; Madhuri Kanakagiri (Journal of Indian Academy of Oral Medicine and Radiology, 2019)
Introduction: The mental foramen (MF) opens on the lateral aspect of the mandible near premolar region on both sides of the mandible. The portion of inferior alveolar nerve present anterior to the MF, prior to exiting the canal, is referred to as the anterior loop (AL) of the inferior alveolar nerve. These anatomical variations cannot be evaluated by conventional imaging techniques. Cone beam computed tomography (CBCT) provides three-dimensional reliable images of maxilla–mandibular region. Hence, it plays an important role to detect and evaluate these anatomical variations and to prevent intra- and postoperative complications. Materials and Methods: This retrospective observational study includes 500 CBCT images of the mandible. The average size, location, shape of MF, and presence of AL were assessed in sagittal, tangential, and axial sections. Results: Out of 250 CBCT scans analyzed, 132 scans (52.8%) were of males and 118 scans (47.2%) belonged to females. The mean size of MF as measured in the sagittal sections was found to be 3.36 mm in height and 2.54 mm in length. The most common position for the MF related to the mandibular teeth in this study was between first and second premolars in 310 CBCT images (62%). A majority of the MF were oval in shape (n = 346, 69.2%) followed by round shape (n = 154, 30.8%). The presence of AL of inferior alveolar nerve was found in only 20% (n = 100) of cases in this study. Conclusion: Considering these variations in MF and AL, the use of CBCT seems necessary for better evaluation and treatment planning.